The relationship between age and running time in elite marathoners is U-shaped - Lara, Beatriz (Springer Netherlands, 2014)
Several investigations have demonstrated that running performance gradually decreases with age by using runners >25 years grouped in 5-year age brackets. The aim of this study was to determine the relationship between race time in marathon and age in elite marathoners by including all ages and 1-year intervals. Running times of the top ten men and women at 1-year intervals (from 18 to 75 years) in the New York City marathon were analyzed for the 2010 and 2011 races. Gender differences in performance times were analyzed between 18 and 70 years of age. The relationship between running time and runner's age was U-shaped: the lowest race time was obtained at 27 years (149 ± 14 min) in men and at 29 years (169 ± 17 min) in women. Before this age (e.g., 27 years for men and 29 years for women), running time increased by 4.4 ± 4.0 % per year in men and 4.4 ± 4.3 % per year in women. From this age on, running time increased by 2.4 ± 8.1 % per year in men and 2.5 ± 9.9 % per year in women. The sex difference in running time remained stable at ~18.7 ± 3.1 % from 18 to 57 years of age. After this, sex difference progressively increased with advancing age. In summary, endurance runners obtained their best performance in the marathon at 27 years in men and 29 in women. Thus, elite marathon runners should program their long-term training to obtain maximal performance during their late 20s.